Marital Psycho-Spiritual Intervention (MP-SI): An Intervention for Blessing Marriage Relationships (Jurnal Pembangunan Sosial, 2018)
This article presents the Marital Psycho-Spiritual Intervention (MP-SI), which provides the married couples and helping professionals with knowledge and skills for strengthening marriage relationships. MP-SI is an intervention that specifically developed to help Muslim married couples build a close relationship with Allah SWT, with themselves, and with their respective couples. This intervention is a structured format. In each session, the participants are exposed to the knowledge of Islamic marriage. The content of this intervention takes into account the content of the Holy Quran on man’s creation, which consisted of four important elements, nafs (soul), aql (intellect), qalb (heart), and ruh (spirit). The participants are exposed to effective communication skills, worked as teams to resolve problems, managed conflicts without decreasing closeness, preserved, and enhanced attachment through communication elements, conflict resolutions, forgiveness, sakinah (tranquility), mawaddah (love with passion), and rahmah (mercy). This intervention may be applied in counseling, relationship education, and couples’ workshops.